Immunological and preventive effects of COVID-19 vaccine against Omicron variant - a review of research progress - Zhi-qiang CAO; Li LU; Wei ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant in November 2021, the coronavirus diseases 2019 (COVID-19) epidemics caused by the variant has rapidly spread all over the world and the variant become the dominant strain in SARS-CoV-2 infections. Under the Omicron variant-induced pandemic, the effects of COVID-19 vaccine based on the ancestral strain has been brought to researches' attention around the world and many scholars have carried out researches on the immunological and preventive effects of different COVID-19 vaccines on the Omicron variant and immunization strategies. Reviewing literatures published from November 1st, 2021 to July 26th, 2022, the study systematically discussed immunological and preventive effects of COVID-19 vaccines on Omicron variant infections for providing a reference to public health decisions such as vaccination strategy optimization and research development.